Safety and Adverse Events Related to Inactivated COVID-19 Vaccines and Novavax; a Systematic Review - Dadras, Omid; Mehraeen, Esmaeil; Karimi, Amirali; M. Tantuoyir, Marcarious; Afzalian, Arian; Nazarian, Newsha; Mojdeganlou, Hengameh; Mirzapour, Pegah; Shamsabadi, Ahmadreza; Dashti, Mohsen; Ghasemzadeh, Afsaneh; Vahedi, Farzin; et al. (Archives of Academic Emergency Medicine, 2022)
Introduction: Knowledge of the safety of vaccines is crucial, both to prevent and cure them and to decrease the public hesitation in receiving vaccines. Therefore, this study aimed to systematically review the adverse events reported for inactivated vaccines and Novavax. Methods: In this systematic review, the databases of PubMed, Scopus, Cochrane, and Web of Science were searched on September 15, 2021. Then we identified the eligible studies using a two-step title/abstract and full-text screening process. Data on the subjects, studies, and types of adverse events were extracted and entered in a word table, including serious, mild, local, and systemic adverse events as well as the timing of side effects’ appearance. Results: Adverse effects of inactivated coronavirus vaccines side effects were reported from phases 1, 2, and 3 of the vaccine trials. The most common local side effects included injection site pain and swelling, redness, and pruritus. Meanwhile, fatigue, headache, muscle pain, fever, and gastrointestinal symptoms including abdominal pain and diarrhea were among the most common systemic adverse effects. Conclusion: This systematic review indicates that inactivated COVID-19 vaccines, including Sinovac, Sinopharm, and Bharat Biotech, as well as the protein subunit vaccines (Novavax) can be considered as safe choices due to having milder side effects and fewer severe life-threatening adverse events.